Molecular Engineering of "Click"‐Phospholes Towards Self‐Assembled Luminescent Soft Materials. (8th August 2013) - He, Xiaoming; Lin, Jian‐Bin; Kan, Wang Hay; Dong, Pengcheng; Trudel, Simon; Baumgartner, Thomas
<x xml:space="preserve">Abstract</x> Inspired by the self‐assembled bilayer structures of natural amphiphilic phospholipids, a new class of highly luminescent "click"‐phospholes with exocyclic alkynyl group at the phosphorus center is reported. These molecules can be easily functionalized with a self‐assembly group to generate neutral "phosphole‐lipids". This novel approach retains the versatile reactivity of the phosphorus center, allowing further engineering of the photophysical and self‐assembly properties of the materials at a molecular level. The results of this study highlight the importance of being able to balance weak intermolecular interactions for controlling the self‐assembly properties of soft materials. Only molecules with the appropriate set of intermolecular arrangement/interactions show both organogel and liquid crystal mesophases with well‐ordered microstructures. Moreover, an efficient energy transfer of the luminescent materials is demonstrated and applied in the detection of organic solvent vapors.